The photocatalytic degradation of phenol and chlorophenol onto bismuth vanadate powder prepared by the solvothermal method - Pookmanee P. (2014)
Bismuth vanadate (BiVO4) powder was prepared by the solvothermal method. Bismuth nitrate and ammonium vanadate were used as the starting precursors with mole ratio of 1:1. The mixed solution was heated in the solvothermal vessel at 100°C for 2-6 h. The phase of BiVO4 powder was characterized by X-ray diffractometer (XRD). The morphology and chemical composition of BiVO4 powder were investigated by scanning electron microscope (SEM) and energy dispersive X-ray spectroscope (EDXS). The surface area of BiVO4 powder was determined by Brunauer, Emmett and Teller analyzer (BET). The photocatalytic degradation of phenol and chlorophenol onto BiVO4 powder was studied and determined by gas chromatograph (GC). © 2013 Copyright Taylor and Francis Group, LLC.